Prevalence of Non-Communicable Diseases Among Elderly in India: A Scoping Review - Patlolla Sriram Yadav; Ajitha Katta; Gooty Shirisha; Mousami Kirtania (National Journal of Community Medicine)
Background: Non-communicable diseases (NCDs) are a growing concern for India's aging population. This scoping review aimed to identify and summarize the prevalence of NCDs among elderly people in India.